An STATCOM-based Hybrid Shunt Compensation Scheme Capable of Damping Subsynchronous Resonance - F. Reyhaneh Mehdizadeh; Daryoush Nazarpour (Institute of Advanced Engineering and Science, 2017)
The paper presents the potential use of supplemental control of a new economical phase imbalanced shunt compensation concept for damping sub synchronous resonance (SSR) oscillations. In this scheme, the shunt capacitive compensation in one phase is created by using a Single-Phase Static Synchronous Compensator (STATCOM) in parallel with a fixed capacitor (Cc), and the other two phases are compensated by fixed shunt capacitor (C). The proposed arrangement would, certainly, be economically attractive when compared with a full three-phase STATCOM which have been used/proposed for power swings and SSR damping. SSR mitigation is achieved by introducing a supplemental signal into the control loops of single phase STATCOM. The validity and effectiveness of the proposed structure and supplemental control are demonstrated on a modified version of the IEEE second benchmark model for computer simulation of sub synchronous resonance by means of time domain simulation analysis using the Matlab program.